Determination of Mycoplasma bovis specific antibodies in blood sera of asymptomatic carriers-calves in three farms in the Republic of Serbia by using indirect ELISA assay - VOJINOVIĆ, D.; VASIĆ, A.; ŽUTIĆ, J.; DURIČIĆ, B.; ILIĆ, Z.; JOVIČIĆ, D.; RADOVANOVIĆ, M. E. (Journal of the Hellenic Veterinary Medical Society, 2017)
Blood serum samples of asymptomatic carriers-calves were collected from three farms in the territory of the Republic of Serbia during 2011 and 2012. Commercial Mycoplasma bovis ELISA kit (Bio-X Diagnostics, Belgique) for serological diagnosis from cattle blood sera and milk was used in this research. Calves’ blood sera were tested using immunoenzymatic indirect ELISA assay as described by manufacturer’s instructions. From 5603 blood sera of asymptomatic carriers-calves 144 (2,57%) samples were tested positive for the presence of specific Mycoplasma bovis antibodies. In three different farms proportions of seropositive samples varied from 0,32% to 10,6% in regard to total number of tested samples from the individual farms. In this paper we present the results of Mycoplasma bovis prevalence in asymptomatic carriers-calves.